Bringing it All Together: Integrating Services to Address Homelessness - Alina Turner; Diana Krecsy (The School of Public Policy Publications, 2019)
Homeless-serving systems are striving for greater impact and efficiency amidst austerity. Those with lived experience, governments, funders, and service providers have consistently and increasingly called for enhanced integration across services, organizations, systems, processes and policies as a means of maximizing existing resources. Here, the discourse of integration refers to ways of working better together across diverse internal and external organizational boundaries. At the heart of these efforts lies the assumption that integration is the desired state, an ideal that will result in improved outcomes at individual and population levels.